Research through service: Meeting Chinese international college students’ mental health needs - Duan, Changming; Chen, Jingru; Li, Fenglan; Zhou, Mi; Lin, Xiubin; Li, Shengnan (Frontiers in Education, 2025)
Introduction and backgroundResearch indicates that Chinese International College Students (CICS) encounter considerable cultural and mental health challenges while studying in the United States. However, there has been limited focus on the processes and outcomes of effective mental health intervention programs tailored to their needs. This study adopted a research-through-service approach to design, implement, and evaluate a four-week group intervention program aimed at enhancing the mental health and well-being of CICS.Methods and intervention programThe group intervention was designed with the perspective that effective mental health services for CICS should be culturally specific, growth-oriented, and focused on promoting positive learning outcomes rather than merely addressing problems or solutions. Group sessions were conducted in Chinese and emphasized experiential activities aimed at enhancing participants’ cultural confidence and fostering a growth-oriented, positive mindset. Thirteen CICS voluntarily participated in the group intervention. One to three weeks after the program, twelve participants took part in semi-structured post-group interviews. These interviews explored their reflections on the group experience, their general perspectives on well-being, perceived challenges and strategies for managing those challenges, and their attitudes toward seeking professional help when needed. The interview data were analyzed using the Consensus Qualitative Research (CQR) method (Hill, 2012).ResultsParticipants shared experiences of cultural conflicts and challenges they faced, as well as the active coping strategies they employed. These strategies included confiding in trusted individuals, practicing forbearance and self-regulation, and seeking practical solutions to underlying problems. When reflecting on the group intervention experience, participants reported notable benefits across intellectual, relational, and emotional domains. Additionally, they provided valuable suggestions for enhancing the program’s effectiveness.ConclusionIntervention programs designed to support Chinese International College Students (CICS) should promote cultural confidence, adopt a strength-based and growth-oriented approach, and avoid deficit-focused or problem-centered frameworks.